European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: stomata; taxonomy; Trichomes; waxes

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
Keywords: stomata; taxonomy; Trichomes; waxes